2019
DOI: 10.17711/sm.0185-3325.2019.005
|View full text |Cite
|
Sign up to set email alerts
|

Social cognition and executive function in borderline personality disorder: evidence of altered cognitive processes

Abstract: Introduction. Social cognition (SC) and executive function (EF) research in borderline personality disorder (BPD) has proven to be controversial and lack of sufficient information about deficit patterns. Objective. Assess the contribution of SC and EF in the socio-emotional and cognitive patterns in BPD, as well as investigate the possible relationships between SC, EF, and clinic features in BPD. Method. The study evaluated 20 females with BPD in ambulatory hospitalization and 20 healthy women in social cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 54 publications
0
10
0
2
Order By: Relevance
“…Four studies reported lower, 80 , 89 , 98 , 101 and three studies reported higher, 48 , 73 , 88 RMET total scores in patients with BPD relative to healthy control subjects, but six studies did not find a significant difference between patients and controls in the RMET total score. 36 , 47 , 61 , 78 , 91 , 99 Schilling and colleagues 47 reported a pattern of high confidence ratings for correct and incorrect answers in patients.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…Four studies reported lower, 80 , 89 , 98 , 101 and three studies reported higher, 48 , 73 , 88 RMET total scores in patients with BPD relative to healthy control subjects, but six studies did not find a significant difference between patients and controls in the RMET total score. 36 , 47 , 61 , 78 , 91 , 99 Schilling and colleagues 47 reported a pattern of high confidence ratings for correct and incorrect answers in patients.…”
Section: Resultsmentioning
confidence: 83%
“…Forty-five studies, published between 2000 and 2019, were included in this review. 17 , 36 , 40 , 41 , 47 , 48 , 52 , 54 57 , 61 , 63 , 69 , 70 , 72 101 Thirteen (28.9%) of the 45 studies comprised samples of patients with psychiatric conditions other than BPD, 40 , 41 , 52 , 55 , 72 , 74 , 77 , 81 , 82 , 87 , 91 , 97 , 100 including other personality disorders, major depressive disorder (MDD), attention-deficit/hyperactivity disorder (ADHD), schizophrenia, substance abuse disorder, and anorexia nervosa (Tables 1 – 4 and 6 – 10 ). All but two studies 47 , 82 reported sex distributions for patients with the diagnosis of BDP.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations